The Mirror Never Lies Laut Bercermin - Yvonne Michalik (Tree Water dan Rumah Sinema, 2016)
Wakatobi, surga laut yang berhasil terangkat ke permukaan. Selama 4 tahun, saya mencoba membantu Wakatobi menunjukkan keindahan yang tersembunyi. Terima kasih atas kerjasama yang baik untuk film The Mirror Never Lies, khususnya masyarakat Wakatobi yang telah memberi dukungan penuh. Juga kepada WWF Indonesia yang telah mendukung ruang kreatif sebagai bentuk partisipasi terhadap konservasi alam. Berharap lewat film dan buku ini, semakin banyak orang yang menghargai serta menjaga ekosistem bawah laut kita. Melalui karya, kita berbagi kepedulian terhadap alam bawah laut Indonesia. Pakis (Gita Novalista) is a young girl from a fishing community of the Bajau people in Wakatobi, Sulawesi, part of the Coral Triangle. She lives with her mother, Tayung (Atiqah Hasiholan). As Pakis' father has been lost at sea, Tayung works hard to support her daughter. Pakis, however, is determined to search for her father, a quest which brings the two into conflict. Pakis regularly visits a local shaman, who conducts a ritual allowing Pakis to search for her father in a mirror's surface. The ritual never shows Pakis his location but she remains determined to keep trying. Meanwhile, Tudo (Reza Rahadian) has broken up with his fiancÃ©e. Struggling to cope with the loss, he takes a new job in Wakatobi studying dolphins. There he becomes involved with the Bajau community, staying at Tayung's home. Eventually Pakis is able to realise that her father is dead and continues with her life.